Temperament vs. chronic fatigue in police officers - Ewa Stępka; Małgorzata Anna Basińska (Nofer Institute of Occupational Medicine, 2015)
Background: Chronic fatigue is a problem affecting a still growing number of people. Among them there are representatives of different professions who are forced to cope not only with occupational stress, but also with the problem of fatigue. The police is one of such occupational groups, in which exposure to stressful and often traumatic situations, contact with those who violate the law, shift work and contact with superiors can play a key role in the development of chronic fatigue. However, chronic fatigue, induced by the above mentioned factors, does not affect all police officers since its occurrence also depends on many personal traits, including temperament. Material and methods: We studied a group of 61 police officers of the Kuyavian-Pomeranian garrison. The study was conducted using the Buss and Plomin EAS (emotionality, activity, sociability) Temperament Questionnaire, CIS-20R (community, innovation, survey) Questionnaire, developed by Vercoulen et al. and a questionnaire on socio-demographic data. Results: The results indicated the relationship between chronic fatigue and emotionality. Statistical analyses showed a negative correlation between the nature of emotional components, distress, fear, anger, and the general rate of chronic fatigue. There was no statistically significant correlation between age, and service experience and the level of chronic fatigue. Conclusions: The results indicate that the officers of the study group show dramatically high levels of chronic fatigue. The results also revealed that temperament characteristics, such as sociability and activity, reported in the literature as factors reducing fatigue and stress, did not show relevance to chronic fatigue in the study group. Med Pr 2015;66(6):793-801